Interactive Crossword Puzzles as an Adjunct Tool in Teaching Undergraduate Dental Students - Abubaker Qutieshat; Nutayla Al-Harthy; Gurdeep Singh; Viresh Chopra; Rayhana Aouididi; Rayan Arfaoui; Sapna Dileesh; Ahmed Alsadoon; Omaima Al-Nadhiri; Shima Al-Busaidi; Sumaiya Al-Rashdi; Mohammad S Alrashdan (International Journal of Dentistry)
Background. In the restorative dentistry module of the undergraduate dental program, dental students encounter many new terms and concepts in a short period of time. The provision of adequate learning support to reinforce key concepts can be challenging. Aim. The purpose of this study is to determine student perceptions of how effective interactive crossword puzzles are as adjunctive tools to enhance the learning of restorative dentistry. Methods. Students completed interactive crossword puzzles created by the authors, with a reward awarded to the first group of students who completed the puzzles successfully. The interactive crossword platform was programmed using the ReactJS framework and designed using Tailwind CSS. An evaluation of the student's perception of this educational method was conducted using textual feedback and Likert-scale questionnaires. Results. Students found the crossword puzzles engaging, meaningful, and successful as indicated by their favorable Likert scores and feedback. Written comments revealed student enthusiasm for and a desire to be exposed to more of these exercises. Conclusions. This work sheds light on the potential advantages of incorporating interactive crossword puzzles into the restorative dentistry course from a student’s perspective. The crossword puzzles improved students’ ability to review and reinforce concepts and terminology and proved to be meaningful and enjoyable. The web-based nature of the tool ensured good student responsiveness and engaged the entire class in an interactive, competitive setting. Application of the hint option, which offered a text of relevant reading material, helped students understand, retain more knowledge, and engage with course material more than they might have otherwise.